'Interpretive genres' in natural history : a socio-cognitive perspective / Yee Chee Leong - Yee, Chee Leong (2012)
This study is an interdisciplinary research that analyses written discourses in natural history through the genre analysis’ lens. Genres are explored and examined by drawing on insights gathered from different disciplines such as linguistics, communication and environmental humanities. Data collected comprise a corpus of selected natural history texts published by the Malaysian Nature Society, Malaysia’s oldest non-governmental environmental and conservation body. Multiple conceptual and analytical models are combined to examine these resources from a socio-cognitive perspective: Bhatia’s (2004) multidimensional and multi-perspective model for professional discourse analysis and the notion of ‘generic integrity’; Tilden’s (1957) principles of interpretation; and Leftridge’s (2002) introduction of ‘interpretive writing’ as a distinct genre. Research methods employed for this study are text analysis and non- and participatory observations. Findings reveal that a new breed of genre colony known as ‘interpretive genres’ exists among the discourses in natural history. Genres belonging to this family serve to achieve communicative purposes that are both goal-directed and pro-social, driven by disciplinary cultures and professional practices of the discourse community. It seems that ‘interpretive genres’ do not merely communicate facts, but also convey subtle meanings by making intellectual and emotional connections between the inherent meanings in natural resources and audience interests and experiences. Results discussed have practical implications for genre-based pedagogy, professional training and development, environmental communication and interpretation, as well as foster nature appreciation through public understanding of ‘interpretive genres’.